Cephalometric evaluation of skeletal relationships after bimaxillary surgical correction of mandibular prognathism - Sinobad, Vladimir; Strajnić, Ljiljana; Sinobad, Tamara (Vojnosanitetski pregled, 2021)
Background/Aim. In recent years, bimaxillary surgery has widely been accepted as an effective surgical procedure for the correction of mandibular prognathism. The aim of this study was to determine how bimaxillary surgical correction can change the skeletal dimensions and relations typical of mandibular prognathism and whether the postoperative results can be compared with biometric values of these dimensions in subjects with normal occlusion. Methods. The study included 50 subjects divided into two groups. The analyzed group consisted of 20 patients with mandibular prognathism, mean age 19.8 ± 5.3 years. The control group consisted of 30 subjects with skeletal class I and normal occlusion, mean age 21.5 ± 3.5 years. Cephalometric studies were conducted on 70 lateral cephalograms made on subjects of the analyzed group before and after surgery and in controls. All radiographs were transformed into a digital form. Using the computer program "Dr. Ceph", 30 linear and angular skeletal variables were analyzed and compared on each radiograph. The values of examined variables in the analyzed group were compared before and after surgery and with the values of the same variables in the control group. Results. Bimaxillary osteotomies changed most of the variables that characterize the mandibular prognathism. Changes in the sagittal plane were reflected in a significant increase of angles SNA (by 4° on the average), ANB (6°), and a significant reduction in angles SNB (3°), ArGoMe (8°), NGoMe (6.2°), Bjork’s sum (7°) and the angle of skeletal convexity NAPg (2°). Changes in vertical relationships were reflected in a significant reduction in overall anterior face height N-Me (by 5 mm on average), the lower anterior face height ANS-Me (4 mm), in a significant increase in the total posterior face height S-Go (2.5–3 mm), lower posterior face height PNS-Go (4 mm), in a significant reduction of the basal angle PP/MP (5°) and angle that mandibular plane closes with the anterior cranial base NS/MP (4°). Comparison of investigated variables in the analyzed group after surgery with the same values in the control group showed that they were significantly closer to biometric standards. Conclusion. Bimaxillary surgery significantly alters the skeletal relationships and facial dimensions typical of mandibular prognathism and normalizes the skeletal profile and appearance in operated patients.
Keywords: malocclusion, angle class III; cephalometry; oral surgical procedures; orthognathic surgical procedures; treatment outcome